Gestão de risco ambiental em usina sucroenergética: estudo qualitativo por matriz de interação - Oliveira, Caroline Grizzo Martiniano de (Universidade Federal de São Carlos, 2024)
The growing demand for energy, coupled with the search for sustainable alternatives to fossil fuels, has put the sugar-energy industry at the center of discussions on economic and environmental development. The production of sugar and ethanol from sugar cane offers significant opportunities for reducing greenhouse gas (GHG) emissions and mitigating climate change. This industry plays a key role in the Brazilian economy, contributing significantly to job creation and export earnings. However, it is also associated with a number of adverse environmental impacts, including water pollution, soil manipulation, emissions of polluting gases into the atmosphere - such as carbon dioxide (CO2) - and the intensive consumption of natural resources. Proper management of these environmental risks is essential not only to comply with environmental regulations, but also to maintain sustainability of the industry and its social license to operate. Thus, this paper explores the topic of environmental risk management in sugar-energy plants, analyzing the challenges, strategies and practices associated with minimizing negative impacts on the environment. The object of study was a Sugar-Energy Plant X located in the interior of São Paulo and the visit made for the work took place in October 2023 during the 2023/2024 harvest. The Interaction Matrix method was used to identify and classify environmental aspects and risks using criteria that assess the occurrence of the event, the severity and the degree of detection. severity and degree of detection. The results showed that the sugar-energy plant has a high level of detection of the environmental risks that may occur, showing that it has ample capacity and speed to adopt measures to reduce pollution of water, the atmosphere and the soil, as well as making conscious use of natural resources in its processes. A environmental risk analysis proved to be satisfactory for the process analyzed, mainly through the application of the Interaction Matrix method.
Environmental risk management in a sugar-energy plant: a qualitative study using an interaction matrix
Keywords: Usinas sucroenergéticas; Gestão de risco ambiental; Mitigação das mudanças climáticas; Sustentabilidade; Método de matriz de interação; Sugar-energy plants; Environmental risk management; Mitigation of climate change; Sustainability; Interaction matrix method; ENGENHARIAS::ENGENHARIA QUIMICA